PROFITABILITY, LIQUIDITY, AND CAPITAL STRUCTURE AS DETERMINANTS OF FIRM VALUE: A STUDY OF TECHNOLOGY COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE (IDX) (2020-2022) - Ni Nyoman Sritapayanti; I Gusti Ngurah Bagus Gunadi; Agus Wahyudi Salasa Gama (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2025)
In general, companies are established with specific objectives, one of which is to increase company value as a long-term goal. High company value can be beneficial for the company and its shareholders. This study aims to examine and obtain empirical evidence of the influence of profitability, liquidity, and capital structure on company value in technology companies listed on the Indonesia Stock Exchange from 2020 to 2022. The population of this study consists of all technology companies listed on the Indonesia Stock Exchange from 2020 to 2022. The research sample was selected using purposive sampling. The sample in this study consisted of 19 technology companies, bringing the total sample size to 57. This study used multiple linear regression analysis. The results of this study indicate that profitability and liquidity have a significant positive effect on company value, while capital structure has no effect on company value in technology companies listed on the Indonesia Stock Exchange from 2020 to 2022.